'When I asked for help and support it was not there': current NHS employment practice and its impact on people with systemic lupus erythematosus. Issue 1 (12th March 2021) - Booth, Sara; Price, Elizabeth; Walker, Elizabeth
Abstract: Objectives: The aim was to investigate whether National Health Service (NHS) employees with SLE, for whom work disability and early retirement are high, are supported effectively in at work. Methods: An online survey of 393 people with lupus was completed through the LUPUS UK website, investigating participants' experiences in maintaining employment. Quantitative and qualitative data were collected. Disease fluctuation, invisibility and fatigue were identified as having substantial negative impacts on employment. This study examined data from a large subgroup ( n = 72, 18.74%) of current/previous NHS employees. Descriptive statistics and thematic analysis were used to explore and characterize the demography and experiences of participants. Results: The NHS subgroup ( n = 72) represented 18.74% of the whole cohort; 100% were female and of working age (18–64 years). Fifty-one were currently (70.8%) and 21 previously (29.2%) NHS employees. Forty-nine (60%) were clinicians. Twenty-one (29.16%) of this working-age subgroup had left any employment. Negative effects of SLE on employment were universal (including an impact on career choices, work disability, enforced part-time working, lower income and early retirement). NHS support for participants to maintain employment was inconsistent, with more negative experiences than positive. The impact of SLE on employment seemed to be poorly understood. Conclusion: A punitive approach to NHS employees with SLE was more common than a proactive, flexible, problem-solving one despite inclusive rhetoric, resulting in the loss of skills and experience to the service. Characterizing conditions such as SLE and long coronavirus disease 2019 as fluctuating, invisible conditions with constitutional symptoms highlights features with negative employment impact, potentially facilitating much-needed change in NHS organizations, with greater use of occupational health, vocational rehabilitation, redeployment and retraining opportunities, highlighting the need for evidence-based employment interventions and improved management of fatigue.